Vaccination effects on post-infection outcomes in the Omicron BA.2 outbreak in Shanghai. Issue 1 (31st December 2023) - Wu, Qianhui; Wang, Hongyu; Cai, Jianpeng; Ai, Jingwen; Li, Yang; Zhang, Haocheng; Wang, Sen; Sun, Feng; Wu, Yanpeng; Zhou, Jiaxin; Wang, Yan; Yu, Hongjie; et al.
ABSTRACT: Omicron and its sublineages are currently predominant and have triggered epidemiological waves of SARS-CoV-2 around the world due to their high transmissibility and strong immune escape ability. Vaccines are key measures to control the COVID-19 burden. Omicron BA.2 caused a large-scale outbreak in Shanghai since March 2022 and resulted in over 0.6 million laboratory-confirmed infections. The vaccine coverage of primary immunization among residents aged 3 years and older in Shanghai exceeded 90%, and inactivated COVID-19 vaccines were mainly delivered. In the context of high vaccine coverage, we conducted a cohort study to assess vaccine effects on reducing the probability of developing symptoms or severity of disease in infections or nonsevere cases. A total of 48, 243 eligible participants were included in this study, the majority of whom had asymptomatic infections (31.0%) and mild-to-moderate illness (67.9%). Domestically developed COVID-19 vaccines provide limited protection to prevent asymptomatic infection from developing into mild-to-moderate illness and durable protection to prevent nonsevere illness from progressing to severe illness caused by Omicron BA.2. Partial vaccination fails to provide effective protection in any situation. The level of vaccine effects on disease progression in the elderly over 80 years old was relatively lower compared with other age groups. Our study results added robust evidence for the vaccine performance against Omicron infection and could improve vaccine confidence.